Inovasi Kepemimpinan Kepala Madrasah dalam Menerapkan Kurikulum Merdeka - Baiq Ida Astini; Aqodiah Aqodiah; Niswatun Hasanah (Fakultas Agama Islam Universitas Billfath, 2023)
The aims of this study are: 1) To describe the concept of madrasa principal leadership, 2) madrasa principal leadership governance, 3) madrasa principal leadership innovation and 4) challenges faced by madrasah principals in implementing the independent learning curriculum. This study uses a qualitative method with a descriptive approach. Data was collected by means of interviews, observation and documentation. The results of the research are the head of MIN 1 Mataram in Implementing the Independent Learning Curriculum, which is to return students to their rights as human beings as the implementation of humanism education where schools are expected to accommodate students according to their interests because each child has their own uniqueness and preferential treatment that makes that uniqueness unique. valuable and meaningful. The innovations made by the Head of MIN 1 Mataram in the context of implementing the learning curriculum, including: 1) increasing the professionalism of human resources, especially teachers at MIN I Mataram, 2) increasing the ability to supervise learning guided by the supervision instrument 3) Innovation related to governance management using the term division, and increased the number of divisions to 11 divisions, namely: a) Curriculum Division, b) Partnership Division (Humas), c) Language Development Division, d) Language Development Division, e) Library Division, f) Religious Division, g) Sports and Health, h) Infrastructure Division, i) UKS/Health Division, j) Arts and Culture Division, k) Security and Order Division